PENGARUH CELEBRITY ENDORSEMENT TERHADAP PURCHASE INTENTION MELALUI PERCEIVED VALUE PADA PRODUK TOP COFFEE DI SURABAYA - HANSUDOH, STEVEN AGUSTINUS (Universitas Katolik Widya Mandala Surabaya, 2012)
The purpose of this study was to find out the influence of Celebrity Endorsement on Purchase Intention through Perceived Value to the â€œTop Coffeeâ€ product in Surabaya. Population in this research is people who understand advertising top coffee version Iwan Fals and have not buy coffee brand Top Coffee. The technique of the sample used is non probability sampling. Analysis techniques used in this research is Structural Equation Modeling (SEM). The results showed that Celebrity Endorsement influence positively to Perceived Value, Celebrity Endorsement influence positively to Purchase Intention, Perceived Value influence positively to the Purchase Intention, and perceived value mediate influence between Celebrity Endorsement to Purchase Intention. A summary of this research is the Celebrity Endorsement, that the use of celebrities in advertising delivery is capable of influencing the value of the product being advertised and are able to influence consumer buying intentions to the product Top Coffee in Surabaya.